2023
DOI: 10.1186/s13018-023-03558-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of more than 50,000 ankle fractures in the Swedish Fracture Register during a period of 10 years

Abstract: Background Despite being one of the most common types of fracture, there is a lack of epidemiological studies involving ankle fractures of all kinds. Since 2012, the Swedish Fracture Register (SFR) has prospectively collected data on surgically and non-surgically treated ankle fractures. The aim of this study is to describe the epidemiology of ankle fractures between 2012 and 2022. Methods All ankle fractures registered in the SFR between 1 April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
1
15
0
2
Order By: Relevance
“…This may correspond to the relatively high reported impairment in PROMs in these groups. Another factor negatively affecting PROMs is the higher incidence of high-energy trauma and open fractures seen in younger patients [ 18 ]. Our study demonstrates that both open injuries and high-energy trauma had a statistically significant negative effect on outcome, and even more so when combined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may correspond to the relatively high reported impairment in PROMs in these groups. Another factor negatively affecting PROMs is the higher incidence of high-energy trauma and open fractures seen in younger patients [ 18 ]. Our study demonstrates that both open injuries and high-energy trauma had a statistically significant negative effect on outcome, and even more so when combined.…”
Section: Discussionmentioning
confidence: 99%
“…This would lead to a higher degree of instability and thereby a more severe injury. However, Rydberg et al demonstrated that patients with C2 fractures had the lowest mean age among all ankle fracture types and C2 was also the fracture type with the largest proportion of open fractures [ 18 ]. This could be one explanation as to why C2 fractures in this study had a greater impairment in PROMs than C3 fractures, because open fractures had a major negative effect on PROMs.…”
Section: Discussionmentioning
confidence: 99%
“…Ankle fractures are one of the most common types of fracture, most commonly occurring in the winter time secondary to falls or sports-related injuries. 27 Although the average age of patients with ankle fractures varies depending on patient sex, incidence typically peaks earlier between 10 and 25 years of age for male patients and later between 70 and 80 years of age for female patients. 27 , 28 , 35 The present study found that the most popular online PEMs regarding ankle fracture are of acceptable quality and meet the NIH recommendation of being written at an eighth-grade reading level.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Although the average age of patients with ankle fractures varies depending on patient sex, incidence typically peaks earlier between 10 and 25 years of age for male patients and later between 70 and 80 years of age for female patients. 27 , 28 , 35 The present study found that the most popular online PEMs regarding ankle fracture are of acceptable quality and meet the NIH recommendation of being written at an eighth-grade reading level. The articles evaluated in this study demonstrated an average quality score of 15.07 with an average FKGL of 8.38.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of tibial fractures in Sweden was 52 per 100,000 per year, with proximal tibial fractures (Figure 1) being the most common tibial fractures, followed by tibial shaft and distal tibial fractures, respectively 26.9, 15.7, and 9.1 per 100,000 per year [1]. The incidence of malleolar fractures in Sweden was 152 per 100,000 per year [2]. In some cases, non-displaced fractures are treated conservatively by immobilization using a cast or brace [3].…”
Section: Introductionmentioning
confidence: 99%